Pengaruh pijat bayi berat lahir rendah terhadap kenaikan berat badan di RSUD Panembahan Senopati Bantul Tahun 2012 - Asmar Yetty Zein; Djaswadi Dasuki; Tunjung Wibowo (Poltekkes Kemenkes Yogyakarta, 2012)
Low birth weight (LBW) babies require more nutrients in order to achieve optimal growth and weight gain is a parameter of success in LBW babies growth. Baby massage for LBW babies is a form of stimulus/tactile kinesthetic stimulation as verbal communication to babies that can increase endurance, the activity of digestive function and activity of the vagus nerves. Good nutritional intake will be able to help weight gain in LBW babies. To determine the benefits of baby massage as a method to enhance weight gain for LBW babies. Method: This was an experimental study with a pretest and posttest control group design and a randomized control design through a quantitative approach. Sample was 60 low birth weight babies born weighing between 1500-2499 grams. The treatment group was given baby massage for 10 days by their mother three times a day and another group were not given treatment. Data analysis was performed by stages from univariable with the frequency distribution characteristics of the respondents, bivariable using independent t-test and RR, and multivariable using logistic regression. Results. the results indicated the effect of baby massage on weight gain as evidenced by t-test value of 0.001 < 0.05. Logistic regression analysis indicated that OR = 2.68. This means that baby massage did affect the weight gain by 2.68. Conclusion: The LBW babies weight gain, treated with massage for 10 days, was higher than those with no such treatment.